The essential schistosome tegumental ectoenzyme SmNPP5 can block NAD-induced T cell apoptosis - Catherine S. Nation (Taylor & Francis Group, 2020)
Infection with intravascular platyhelminths of the genus Schistosoma can result in the debilitating disease schistosomiasis. Schistosomes (blood flukes) can survive in the host for many years. We hypothesize that proteins on their host-interactive surface modify the worm’s external environment to help insure worm survival. Previously, we have shown that a surface ectoenzyme of Schistosoma mansoni, SmNPP5 – a nucleotide pyrophosphatase/phosphodiesterase – can cleave ADP and block platelet aggregation in vitro. In this work, we show that both adult schistosomes and recombinant SmNPP5 can cleave the exogenous purinergic signaling molecule nicotinamide adenine dinucleotide (NAD). In doing so, worms and rSmNPP5 can prevent NAD-induced apoptosis of T cells in vitro. Since regulatory T cells (Tregs) are especially prone to such NAD-induced cell death (NICD), we hypothesize that schistosome cleavage of NAD promotes Treg survival which creates a more immunologically hospitable environment for the worms in vivo. In addition to SmNPP5, schistosomes express another host-interactive NAD-degrading enzyme, SmNACE. We successfully suppressed the expression of SmNPP5 and SmNACE (singly or together) using RNAi. Only SmNPP5-suppressed worms, and not SmNACE-suppressed worms, were significantly impaired in their ability to cleave exogenous NAD compared to controls. Therefore, we contend that ectoenzyme SmNPP5 on the surface of the worm is primarily responsible for extracellular NAD cleavage and that this helps modulate the host immune environment by preventing Treg cell death.